Surface modified nitinol stents release metal ions in blood - Kapnisis, Konstantinos; Eleftheriou, Polyvios; Lapathitis, George; Karaiskos, Christos; Beck, Preston; Lemons, Jack; Connolly, David; Pitsillides, Costas; Anayiotos, Andreas (My University, 2013)
Intravascular nitinol stents are used in the treatment of atherosclerosis and intracranial aneurysms. Despite the unique physical properties of shape memory and superelasticity, the chemical composition of NiTi has raised concerns due to the presence of nickel ions within the alloy which can have adverse effects on human health. Currently, stents are manufactured from corrosion resistant alloys which form protective titanium oxide films, insulating the bulk material from the corrosive physiologic fluid. However, nanometer thick regions of oxides are lost at locations of high strain due to significant bending, micromotion between overlapping stents or local calcification1‐2. Recent studies have revealed that some stents undergo corrosion in vivo, with significant release of metallic ions into surrounding tissues3–4. In this project, a range of techniques has been employed to modify the surface of miniature NiTi stents in order to mimic in vivo corrosion and correlate the amount of nickel ions released with the findings in explanted tissue.
Keywords: Ions; Metals; Blood; Nickel titanium alloys; Stents